UNWIRED PLANET INTERNATIONAL LTD v HUAWEI TECHNOLOGIES CO LTD. Issue 5 (9th August 2018) - ,
Abstract: Patents – European patents – Standards essential patents – Infringement proceedings – Technical trial – Entitlement to priority – Assessing the disclosure of the priority document – The role of common general knowledge – Obviousness – Approach to findings of obviousness on appeal – Secondary evidence – Novelty – Meaning of "before the date of filing" – Applications filed in different time zones – Appeal to Court of Appeal